PENGARUH LEARNING CYCLE 5E TERHADAP LITERASI SAINS PESERTA DIDIK PADA MATERI SISTEM EKSKRESI - Egi Nuryadin (Jurnal Life Science : Jurnal Pendidikan dan Ilmu Pengetahuan Alam, 2019)
ABSTRACTThe purpose of this research to determine the influence Learning Cycle 5E model to student literasi science on system of excretion in class VIII SMP Negeri 14 Tasikmalaya. This study was conducted in Desember 2017 until July 2018 at SMP Negeri 14 Tasikmalaya. The research method that True-experiment, population of the entire class VIII SMP Negeri 14 Tasikmalaya as many as 11 classes, with the amount of learners 387 people. The sample were taken useing cluster random sampling, there are VIII C as an experimental class and VIII B as an control class. To measure student literacy science, the instrument used in the from of literacy science test amounted to 32 items in the from of multiple choice. Technique analysis of data used t test with significant level α 0,05. The results showed there is influence Learning Cycle 5E model to student literasi science on system of excretion in class VIII SMP Negeri 14 Tasikmalaya. Keywords: Learning Cycle 5E, Literasi Science, System Excretion